Keabsahan Mutasi Karyawan tanpa Klausul Mutasi dalam Perjanjian Kerja ditinjau Menurut Undang-Undang Nomor 6 Tahun 2023 tentang Pengesahan Perpu Cipta Kerja (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
Employee transfers are common in companies, but regulations regarding transfer provisions are still very minimal. The absence of specific provisions governing transfers is often misused by employers, resulting in industrial relations disputes, one of which occurred between PT. Amartha Manunggal Prima and Khairunnisa Utami. This study aims to analyze the validity of the transfer process carried out by the company if there are no provisions or legal basis underlying the transfer process. This study uses a normative legal method, by analyzing the conformity between the considerations of the Panel of Judges in Decision Number 24/Pdt.Sus-PHI/PN JMB with laws and regulations, especially Law Number 6 of 2023 concerning the Ratification of the Job Creation. Based on the results of the analysis, a transfer process is one of the company's rights to regulate human resources for the interests and progress of the company and in general transfers are regulated in work agreements, joint work agreements, or company regulations. If the mutation process is not regulated, then the mutation must be based on an agreement between the two parties as mentioned in the Supreme Court Decision Number 567 K/Pdt.Sus-PHI/2016 which stipulates that mutations without the consent of workers can be canceled through the industrial relations court. In addition, mutations must not conflict with existing laws and regulations, especially Article 32 of the Manpower Law which regulates the placement of workers,